Computed Tomography Findings in Intraabdominal Hypertension in Patients with Acute Pancreatitis - Gupta, Pankaj; Kamat, Rohan; Samanta, Jayanta; Mandavdhare, Harshal; Sharma, Vishal; Sinha, Saroj Kant; Dutta, Usha; Kochhar, Rakesh (Indian Journal of Radiology and Imaging, 2021)
Purpose Intraabdominal hypertension (IAH) in acute pancreatitis (AP) may reduce tissue perfusion and impair organ function and has been shown to portend poor prognosis. We investigated the computed tomography (CT) findings in patients with AP with IAH.Methods This retrospective study comprised of consecutive patients with AP from June 2016 to June 2018 in whom intraabdominal pressure (IAP) was measured. The patients who underwent a contrast-enhanced CT within 7 days of IAP measurement were included. Using a cutoff of 12 mm Hg for IAP, the patients were divided into IAH and non-IAH groups. Measures of severity and clinical outcome were evaluated. CT parameters were compared between the groups.Results The IAH group comprised of 41 patients, while there were 20 patients in the non-IAH group. The IAH group was characterized by severe disease, increased incidence of organ failure, increased requirement for drainage and surgery, prolonged hospital and intensive care unit stay. The mortality was not significantly different between the two groups. On univariate analysis, the CT features that were found to be significantly different between the two groups were the presence of collection (p = 0.036), the maximum dimension of collection (p = 0.004), volume of collection (p = 0.019), biliary dilatation (p = 0.011), and the presence of moderate-to-severe pleural effusion (p = 0.009). On multivariate analysis, all these parameters except biliary dilatation were found to be statistically significant.Conclusion CT findings in patients with AP may suggest IAH. This can be used as an additional marker for severity of AP.
Keywords: acute pancreatitis; abdominal compartment syndrome; computed tomography; intraabdominal hypertension